KOPI BAKEDAI DALAM FOTOGRAFI KOMERSIAL - Arsal, Fadhil (Matalensa: Journal of Photography and Media, 2021)
This article  is entitled “bakedai coffee in commercial photography.”  The purpose of this article is to create a commercial photography work about the coffee menu provided at Bakedai. Data collection methods used are: observation, literature study, and interviews. From the observation process that has been carried out by thecraftsmen at Bakedai, Bakedai is here made with comfort and design with an interesting concept that makes visitors not only enjoy coffee but also immerse themselves in the atmosphere there. The method used by the artist when shooting is mix lighting. Mix  lighthing here is a combination of light sources. This technique is used so that the atmosphere at the location of the photographer feels and the image looks more real. Commercial photography is intended for advertising of a product, poster, or other with a point of view that attracts potential consumers.